Language Court and the Stagnation of Foreign Language in the Pesantren: Case Study in Bustanul Ulum Langsa, Aceh - Hatta Sabri; Nasruddin; Ahmad Tarmizi; Hicham Khaldi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
The stagnation of Arabic and English language learning in Islamic boarding schools not only lowers the linguistic proficiency of students but also affects the institution’s reputation. This study aims to analyse the causes of the stagnation in the foreign language environment at Pesantren Bustanul Ulum, Aceh, which appears to stem from the dysfunction of the mahkamah lughah (language court) system. Using a qualitative approach with a case study design, data were collected through in-depth interviews with 24 informants selected through purposive sampling, comprising language coordinators, dormitory supervisors, students (Student Council members and language section representatives), alumni, and parents. Data analysis was conducted thematically. The research findings indicate that the primary factor behind the stagnation of language development is the conflict between the disciplinary sanctions of the ‘mahkamah lughah’ and the Child Protection Act. This obstacle has triggered resistance from parents, the criminalisation or intimidation of teachers, and has resulted in a policy dilemma for the foundation, which tends to adopt a passive stance. This study recommends the need to reconstruct the Mahkamah Lughah system based on positive, child-friendly discipline without compromising the essence of language enforcement.